1994
DOI: 10.1007/bf02050149
|View full text |Cite
|
Sign up to set email alerts
|

Development of invasive adenocarcinoma following colectomy with ileoanal anastomosis for familial polyposis coli

Abstract: We stress the need for lifelong proctoscopic surveillance in patients with familial polyposis coli treated by proctocolectomy with ileoanal anastomosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 18 publications
0
42
0
Order By: Relevance
“…Our review of the literature revealed seven cases of adenocarcinomas developing after restorative proctocolectomy with ileoanal anastomosis documented between 1984 and 1997 [27][28][29][30][31][32][33] (Table 4). Five of these patients were affected by UC, and two by FAP.…”
Section: Discussionmentioning
confidence: 99%
“…Our review of the literature revealed seven cases of adenocarcinomas developing after restorative proctocolectomy with ileoanal anastomosis documented between 1984 and 1997 [27][28][29][30][31][32][33] (Table 4). Five of these patients were affected by UC, and two by FAP.…”
Section: Discussionmentioning
confidence: 99%
“…24 More recently, adenomas have been noted in the ileal pouch after RPC. [25][26][27][28][29] In this study we found that 35% of our patients had adenomas in their ileal pouch, an incidence similar to the 42% reported by Church et al 29 This risk is high considering the life expectancy of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…There have already been three reported cases of cuff cancer in patients with FAP [9][10][11] . Regarding the anal transitional zone, two cancer cases have been reported [1] .…”
Section: Discussionmentioning
confidence: 99%